Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Thanh Thảoo

Cho a = b = c và \(c=\frac{bd}{b-d}\left(b\ne0;d\ne0\right)\)

Chứng minh \(\frac{a}{b}=\frac{c}{d}\)

Kudo Shinichi
6 tháng 10 2019 lúc 6:41

Ta có :

\(c=\frac{bd}{b-d}\)

\(\Rightarrow b-d=\frac{bd}{c}\left(c\ne0\right)\)

\(a=b+c\Rightarrow c=a-b\)

\(\Rightarrow c=\frac{bd}{b-d}=a-b\)

\(\Rightarrow bd=\left(a-b\right).\left(b-d\right)\)

\(\Rightarrow ab-ad-b^2+bd=bd\)

\(\Rightarrow a\left(b-d\right)-b^2=0\)

\(\Rightarrow a.\frac{bd}{c}-b^2=0\)

\(\Rightarrow\frac{ad}{c}-b=0\)

\(\Rightarrow\frac{ad-bc}{c}=0\)

\(\Rightarrow ad-bc=0\)

\(\Rightarrow ad=bc\)

\(\Rightarrow\frac{a}{b}=\frac{c}{d}\left(đpcm\right)\)

Chúc bạn học tốt !!!


Các câu hỏi tương tự
Bùi Quang Vinh
Xem chi tiết
Phạm Hồng Quyên
Xem chi tiết
nguyen van huy
Xem chi tiết
Hoàng Xuân Ngân
Xem chi tiết
Nguyễn Thị Diễm Huyền
Xem chi tiết
Nguyễn Nhật Hạ
Xem chi tiết
nguyễn hoàng mai
Xem chi tiết
The Last Legend
Xem chi tiết
vinh
Xem chi tiết